Root cause analysis of an uncommon surface defect on galvannealed steel sheet. (November 2018) - Mondal, Avik; Halder, Arup Kumar; Nayak, Soumilya; Kumar, Amrendra; Chakraborty, Anindita; Shukla, Shweta; Sahoo, Sibasis; Pais, Rajesh S.; Dutta, Monojit
Abstract: The galvannealed coating has been extensively used in automotive industries because of its superior performance for weldability, paintability and corrosion resistance. However, surface defect of the galvannealed coating is a major concern for the steel manufacturers and the automotive industries. The galvannealing coating process comprises several process steps and each process step may incorporate different types of defects on the coated surface. In the present study, an uncommon surface defect which looks like an indentation mark on the coating surface has been investigated. Scanning Electron Microscopy (SEM) coupled Energy Dispersive X-ray Spectroscopy (EDS) has been used to analyse the morphology and the chemical compositions. Confocal Laser Scanning Microscopy (CLSM) has been used to measure the depth and the morphology of the defect. It was found that the defect was developed on the steel sheet at the end section of the annealing furnace because of mechanical abrasion with rolls. In-depth analysis suggested that zinc vapour from zinc bath were forming zinc oxide particles in the snout region. Zinc oxide particles were able to travel to the end section of the annealing furnace due to improper snout operation. These particles were getting entrapped in-between the roll surface and the steel strip and forming the surface defect on the galvannealed steel surface. Graphical abstract: Unlabelled Image Highlights: A microscopic defect which appears as an indentation mark on galvannealed coating The defect is present on the top and bottom surface of the coated steel sheet Generally, the defect has a shape of 'comma' and shows a typical relationship with rolling direction Defect is generated in the hot bridle zone of annealing furnace due to improper control of HNx gas flow in snout Abrasion of ZnO particle with the steel strip is the root cause of the defect formation